PHYTOCHEMICAL SCREENING AND BIOLOGICAL ACTIVITIES OF BORASSUS FLABELLIFER L. - Singchai, Butsarakham; Kansane, Kumparak; CHOURYKAEW, BOONSANONG (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The extracts and sugar syrup of Borrasus flabellifer L. belonging to family Areaceae reported to be posses the antioxidant and cytotoxic activities. The ethanolic extracts of fruit pulp, seed coat, cotyledon were showed IC50 in antioxidation by DPPH assay at a concentrations of 1.00Â±0.044, 0.900Â±0.044, and 1.40Â±0.217mg/ml, respectively. However, sugar syrup was showed antioxidant with 40% at concentration 2.50 % v/v in methanol, showed percentage of survival of human dermal fibroblast, neomatal (HDFn) C-004-5C cell lines 67.31% at concentration 10.00 % v/v in distill water. The phytochemical analysis carried out revealed the presence of reducing sugar, terpenoids, tannins, flavonoids and coumarin in all extracts, but sugar syrup showed positive only for the presence of reducing sugarÂ Â Keyword: phytochemical, biological activities, Borassus flabellifer L.